The European Monetary Union as a commitment device for new EU member states - Federico Ravenna (European Central Bank (ECB), 2005)
This paper shows that the credibility gain from permanently committing to a fixed exchange rate by joining the European Monetary Union can outweigh the loss from giving up independent monetary policy. When the central bank enjoys only limited credibility a pegged exchange rate regime yields a lower loss compared to an inflation targeting policy, even if this policy ranking would be reversed in a fullcredibility environment. There exists an initial stock of credibility that must be achieved for a policy-maker to adopt inflation targeting over a strict exchange rate targeting regime. Full credibility is not a precondition, but exposure to foreign and financial shocks and high steady state inflation make joining the EMU relatively more attractive for a given level of credibility. The theoretical results are consistent with empirical evidence we provide on the relationship between credibility and monetary regimes using a Bank of England survey of 81 central banks.
Keywords: E52; E31; F02; F41; 330; Credibilty; Exchange Rate Regimes; inflation targeting; monetary policy; open economy; Eurozone; Inflationssteuerung; Geldpolitik; Glaubwürdigkeit; Offene Volkswirtschaft; Wechselkurssystem; EU-Mitgliedschaft